On the Evolution of BM Orionis - Rhorom Priyatikanto (Institut Teknologi Bandung, 2013)
BM Orionis, an eclipsing binary system which is located in the center of Orion Nebula Cluster, posseses several enigmatic problems. Its intrinsic nature and nebular environment make it harder to measure the physical parameters of the system, but it is believed as an Algol-type binary, where the secondary component is a pre-main sequence star with larger radius. To assure this, several stellar models (M1 = 5.9 M¤ and M2 = 2.0 M¤) are created and simulated using MESA. Compared to non-rotating ones, models with rigid rotation of wi = 10-8 rad/s exhibit considerably similar properties during pre-main sequence stage. However, 2.0 M¤ star at assumed age of 106 years is 6.46 times dimmer than the observed secondary star. There must be an external mechanism to fill this luminosity gap. Then, simulated post-main sequence binary evolution of BM Orionis that involves mass transfer shows that primary star will reach helium sequence with the mass of 0.9 M¤ before second stage mass transfer. Keywords: Binary star, Stellar and binary evolution. Evolusi BM Orionis Abstrak BM Orionis, sebuah sistem bintang ganda yang terletak di pusat Orion Nebula Cluster, memiliki beberapa masalah enigmatis. Kondisi intrinsik serta lingkungan yang penuh awan antarbintang membuat pengukuran parameter fisis sistem menjadi makin sulit, tapi sistem ini telah dipercaya sebagai sistem Algol, di mana komponen sekundernya merupakan bintang pra-deret utama dengan radius lebih besar. Untuk memastikan hal ini, beberapa model bintang (M1 = 5,9 M¤ dan M2 = 2,0 M¤) disimulasikan menggunakan MESA. Dibandingkan dengan model tanpa rotasi, model berotasi dengan kecepatan sudut wi = 10-8 rad/s memiliki properti yang hampir sama selama tahap evolusi pra-deret utama. Akan tetapi, model bermassa 2.0 M¤ pada usia 106 tahun 6.46 kali lebih redup dibandingkan bintang sekunder yang teramati. Harus ada mekanisme eksternal untuk menjelaskan kesenjangan luminositas ini. Kemudian, simulasi evolusi lanjut BM Orionis yang melibatkan transfer massa menunjukkan bahwa bintang primer akan mencapai helium sequence dengan massa 0.9 M¤ sebelum transfer massa tahap kedua. Kata kunci: Bintang ganda, Evolusi bintang, Evolusi bintang ganda.